General Self-Efficacy Associations with Personality and Motivation: Psychometric Properties and Measurement Invariance of the Polish New General Self-Efficacy Scale - Baran, Lidia; Janowski, Maciej (Studia Psychologica: Theoria et praxis, 2024)
This study aimed to determine the validity and reliability of the Polish version of the New General Self-Efficacy Scale (NGSE). In four different samples (N = 1,837), adult respondents completed the Polish version of NGSE (NGSEpl) in combination with questionnaires assessing personality, motivation, and behavioral tendencies. Confirmatory factor analysis demonstrated a good fit for the one-factor structure. Cronbach's alpha was above .87 in all samples, and the stability of the scale was .68. Measurement invariance of NGSEpl calculated for different age groups confirmed that the scale measures the same construct in both samples. NGSEpl scores were positively related to the frequency of active coping strategies, mastery-goal orientation, and Big Five model traits and negatively to passive coping strategies. Results supported the reliability, stability, and validity of the NGSEpl.